High Prevalence of Extended-Spectrum Beta-Lactamases in Escherichia coli Strains Collected From Strictly Defined Community-Acquired Urinary Tract Infections in Adults in China: A Multicenter Prospective Clinical Microbiological and Molecular Study - Jia, Peiyao; Zhu, Ying; Li, Xue; Kudinha, Timothy; Yang, Yang; Zhang, Ge; Zhang, Jingjia; Xu, Yingchun; Yang, Qiwen (Frontiers in Microbiology, 2021)
Objectives: To investigate the antimicrobial susceptibility and Extended-spectrum beta-lactamase (ESBL) positive rates of Escherichia coli from community-acquired urinary tract infections (CA-UTIs) in Chinese hospitals. Methods: A total of 809 E. coli isolates from CA-UTIs in 10 hospitals (5 tertiary and 5 secondary hospitals) from different regions of China were collected during the period of 2016 -2017 according to the strict inclusion criteria. Antimicrobial susceptibility testing was carried out by standard broth microdilution method. Isolates were categorized to ESBL-positive, ESBL-negative, and ESBL-uncertain groups according to the CLSI recommended phenotypic screening method. ESBL and AmpC genes were amplified and sequenced on ESBL-positive and ESBL-uncertain isolates. Results: The antimicrobial agents with susceptibility rates of greater than 95% included imipenem (99.9%), colistin (99.6%), ertapenem (98.9%), amikacin (98.3%), cefmetazole (97.9%), nitrofurantoin (96%), and fosfomycin (95.4%). However, susceptibilities to cephalosporins (varying from 58.6%-74.9%) and levofloxacin (48.8%) were relatively low. In the phenotypic detection of ESBLs, ESBL-positive isolates made up 38.07% of E. coli strains isolated from CA-UTIs, whilst 2.97% were ESBL-uncertain. Antimicrobial susceptibilities of imipenem, cefmetazole, colistin, ertapenem, amikacin and nitrofurantoin, against ESBL-producing E. coli strains were greater than 90%. The percentage of ESBL-producing strains was higher in male (53.6%) than in female patients (35.2%) (P<0.001). CTX-M-14 (31.8%) was the major CTX-M variant in the ESBL-producing E. coli, followed by CTX-M-55 (23.4%), CTX-M-15 (17.5%), and CTX-M-27 (13.3%). The prevalence of carbapenem-resistant E. coli among CA-UTI isolates was 0.25% (2/809). Conclusion: Our study indicated high prevalence of ESBL in E. coli strains from strictly-defined community-acquired urinary tract infections in adults in China. Imipenem, colistin, ertapenem, amikacin and nitrofurantoin were the most active antimicrobials against ESBL positive E. coli isolates. blaCTX-M-14 is the predominant esbl gene in ESBL-producing and ESBL-uncertain strains. Our study indicated that the use of cephalosporins and fluoroquinolone needs to be restricted for empirical treatment of CA-UTIs in China.